Effect of Dietary Fats on Glucose Tolerance, Insulin Sensitivity and Membrane Free Fatty Acids in Rats - Alsaif, Mohammed Abdullah (Pakistan Journal of Nutrition, 2003)
The present work was designed to assess the possible effects of n-3 polyunsaturated fatty acid (n-3 PUFA) as fish oil, monounsaturated fatty acid (MUFA) as olive oil (OO), saturated fatty acid (SFA) as butter oil (BO) and their combinations on glucose tolerance, insulin sensitivity and membrane free fatty acid levels. Relatively high fat (20% w/w, 40% energy) content diets were prepared and supplemented to adult male Wistar rats for 5-weeks. Body growth, intravenous glucose tolerance, insulin sensitivity and membrane free fatty acid levels in hepatic cells and erythrocytes were measured. Mean body weights and total body fats were significantly increased in both SFA and MUFA diets fed rats as compared to control and n-3 PUFA dietary groups respectively. Significant impaired glucose tolerance and insulin insensitivity was observed in rats supplemented with SFA diet as compared to all other dietary groups. However, MUFA diet has not shown any significant effect on glucose tolerance and insulin sensitivity, although it significantly induced obesity in rats. The presence of (10%) fish oil in the diet corrected the adiposity affect of SFA and significantly reduced the impairment in glucose tolerance and insulin insensitivity. In conclusion, the results provide evidence that replacing SFA with MUFA is most beneficial even though MUFA promotes the obesity. Fish oil proven the protective effect against the impairment of glucose tolerance, insulin insensitivity and obesity which induced by butter oil.